2010
DOI: 10.1002/jmri.22039
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between in vivo 1H MRS and ex vivo 1H HRMAS metabolite measurements in adult human gliomas

Abstract: Within defined limitations, ex vivo astrocytoma biopsy HRMAS (1)H spectra have similar metabolic profiles to that obtained in vivo and therefore detailed ex vivo characterization of glioma biopsies can directly relate to the original tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…With these resonances, discrimination between PCNSL and high-grade tumours has been successful in more than 82 % (short TE) and 72 % (long TE) of our test cases. Lipid resonances at 1.2 ppm have been related to tumour necrosis [18][19][20]. Although PCNSL is considered a highly malignant tumour, necrosis is not a prominent finding of this highly cellular tumour.…”
Section: Discussionmentioning
confidence: 95%
“…With these resonances, discrimination between PCNSL and high-grade tumours has been successful in more than 82 % (short TE) and 72 % (long TE) of our test cases. Lipid resonances at 1.2 ppm have been related to tumour necrosis [18][19][20]. Although PCNSL is considered a highly malignant tumour, necrosis is not a prominent finding of this highly cellular tumour.…”
Section: Discussionmentioning
confidence: 95%
“…This effect, however, was not shared by all brain regions, as serotonin levels remained stable over an 18-h postmortem interval in the cingulate cortex (25). Furthermore, concentrations of many metabolites, such as myo-inositol, creatine, glutamine, glutamate, N-acetylaspartate, and taurine were shown to remain stable in the postmortem brain tissue over long time intervals (22,23,26,27). Similarly, experiments quantifying brain polyamines, such as spermine, spermidine, and putrescine, in postmortem human brain using GC-MS did not report any significant relationship between these metabolite concentrations and postmortem interval (28).…”
Section: Freely Available Online Through the Pnas Open Access Optionmentioning
confidence: 91%
“…Previous studies that have used proton magnetic resonance spectroscopy in human and rat brain biopsy samples have shown that concentrations of metabolites associated with anaerobic glycolysis, such as glucose, alanine, glutathione and lactate, change after death (21)(22)(23)(24). In rat brain, postmortem delay also leads to concentration changes of dopamine, norepinephrine, and serotonin in the occipital cortex.…”
Section: Freely Available Online Through the Pnas Open Access Optionmentioning
confidence: 99%
“…This study demonstrates very low concentrations of lactate in benign biopsy tissue, which exclude the problem of depletion and ischemia during surgical removal. Several studies using HR MAS on surgically removed tissue discuss tissue oxygen depletion and ischemia investigating lactate as a biomarker [92,95].…”
Section: Lactate Productionmentioning
confidence: 99%
“…Overall, the amount of biochemical information in HR MAS spectra was on the same scale as spectra from tissue extracts. HR MAS has later been applied to human cancers in the brain [10,20,46,47,81,82,86,[89][90][91][92][93][94][95][96][97][98][99][100][101], breast [9,19,38,102], prostate [15,18,[103][104][105][106][107][108][109][110], cervix [40,50,[111][112][113][114], kidney [36,115,116], colorectal [42,43,45,51] and other neoplastic tissues [39,49,…”
Section: Studies Of Chocc In Cancer Using Hr Masmentioning
confidence: 99%